“LAURA” AND THE “LANDLORD”: DOROTHY PETERSON’S FUENTEOVEJUNA - Pawel, Rebecca (ConSecuencias, 2019)
A number of foreign language versions of Lope de Vega's Fuenteovejuna appeared in the 1930s, which reflected the political outlook of both the far left and the far right at the time. Among these translations and adaptations, the one made by Dorothy Peterson for the Harlem Suitcase Theater in 1937 is of special interest. Although her work was intended as an aid for a free verse adaptation by Langston Hughes, this article argues that Peterson's ostensibly “literal” translation made a conscious attempt to link the late-medieval setting of the play with the faux-medieval mythology of the antebellum South, thus exposing the idea of Southern “chivalry” as based on sexual violence. Peterson's translation contains a racial coding of the original drama's characters that would have been immediately intelligible to the Harlem Suitcase Theater's audiences, and which was designed to make a culturally distant work immediately comprehensible and relevant to a specifically African American public. Resumen Varias traducciones de Fuenteovejuna, aparecidas a lo largo de los años treinta, reflejaron tanto una ideología de derecha como de izquierda. La que hizo Dorothy Peterson al inglés en 1937 para el Harlem Suitcase Theater tiene un interés especial. Aunque Peterson en teoría concibió su obra sólo como guía de una adaptación más libre hecha por el poeta Langston Hughes, este artículo sostiene que la traducción “literal” de Peterson hace un intento consciente de conectar la visión de la época medieval del drama de Lope con la mitología medievalista del sur de los EEUU. Peterson revela, así, el vínculo entre el mito de lo “caballeresco” del sur y la violencia sexual. Su traducción implica una codificación racial de los personajes que el público del Harlem Suitcase Theater habría reconocido, y que funciona como mecanismo para asegurar que un drama extranjero fuera relevante y comprensible a un público afroamericano.